Two problems of Ancient Greek Prosody. First part: closed syllables with acute accent - Abritta, Alejandro (AADEC - UNL, 2016)
This paper is the first part of a study on two problems of Ancient Greek prosody, linked with the relation between the tonal accent of the language and the syllabic structure of words. After a sum up of some of the basic concepts of Greek prosody that are used throughout the paper, it analyzes the problem of words with closed syllables marked with acute accent. The main novelty of the analysis (the problem has been previously faced by others) is that the corpus used is the Homeric poetry, until today unattended as a source of evidence for Greek accent.